A stable explant culture of HER2/neu invasive carcinoma supported by alpha-Smooth Muscle Actin expressing stromal cells to evaluate therapeutic agents - Piechocki Marie P (BMC Cancer, 2008)
Abstract Background To gain a better understanding of the effects of therapeutic agents on the tumor microenvironment in invasive cancers, we developed a co-culture model from an invasive lobular carcinoma. Tumor cells expressing HER2/neu organize in nests surrounded by alpha-Smooth Muscle Actin (α-SMA) expressing tumor stroma to resemble the morphology of an invading tumor. This co-culture, Mammary Adenocarcinoma Model (MAM-1) maintains a 1:1 ratio of HER2/neu positive tumor cells to α-SMA-reactive stromal cells and renews this configuration for over 20 passages in vitro. Methods We characterized the cellular elements of the MAM-1 model by microarray analysis, and immunocytochemistry. We developed flow cytometric assays to evaluate the relative responses of the tumor and stroma to the tyrosine kinase inhibitor, Iressa. Results The MAM-1 gene expression profile contains clusters that represent the ErbB-2 breast cancer signature and stroma-specific clusters associated with invasive breast cancers. The stability of this model and the ability to antigenically label the tumor and stromal fractions allowed us to determine the specificity of Iressa, a receptor tyrosine kinase inhibitor, for targeting the tumor cell population. Treatment resulted in a selective dose-dependent reduction in phospho-pMEK1/2 and pp44/42MAPK in tumor cells. Within 24 h the tumor cell fraction was reduced 1.9-fold while the stromal cell fraction increased >3-fold, consistent with specific reductions in phospho-pp44/42 MAPK, MEK1/2 and PCNA in tumor cells and reciprocal increases in the stromal cells. Erosion of the tumor cell nests and augmented growth of the stromal cells resembled a fibrotic response. Conclusion This model demonstrates the specificity of Iressa for HER2/neu expressing tumor cells versus the tumor associated myofibroblasts and is appropriate for delineating effects of therapy on signal transduction in the breast tumor microenvironment and improving strategies that can dually or differentially target the tumor and stromal elements in the microenvironment.